2022
DOI: 10.1186/s12884-022-04632-z
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent pregnancy in Sao Tome and Principe: a cross-sectional hospital-based study

Abstract: Background Pregnancy starts early in Sao Tome and Principe (STP) and rates of adolescent pregnancy increased 16% in recent years reaching a 27.3% prevalence. This study aimed to understand the pregnant adolescents’ characteristics and factors associated to early childbearing in STP. Methods A cross-sectional hospital-based study was undertaken in Hospital Dr. Ayres de Menezes between 2016 and 2018 with a randomly selected total sample size of 518 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
(36 reference statements)
1
12
0
Order By: Relevance
“…These results are in line with studies conducted in Cameroon [69] and Ethiopia [36] as well as published literature that suggests that lower APGAR scores are associated with severe multiorgan damage resulting in brain damage, lung dysfunction, cardiomyopathy, renal failure, hepatic failure, necrotizing enterocolitis and consequently death [70]. Previous studies [23,24] that compared outcomes between adolescent pregnant girls and older counterparts identified that adverse outcomes imputable to adolescent births were fetal distress (OR 1.94, 95% CI 1.18-3.18) and performance of neonatal resuscitation maneuvers (OR 2.4, 95% CI1.07-5.38), highlighting the risks surrounding this period among deliveries at HAM maternity unit.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are in line with studies conducted in Cameroon [69] and Ethiopia [36] as well as published literature that suggests that lower APGAR scores are associated with severe multiorgan damage resulting in brain damage, lung dysfunction, cardiomyopathy, renal failure, hepatic failure, necrotizing enterocolitis and consequently death [70]. Previous studies [23,24] that compared outcomes between adolescent pregnant girls and older counterparts identified that adverse outcomes imputable to adolescent births were fetal distress (OR 1.94, 95% CI 1.18-3.18) and performance of neonatal resuscitation maneuvers (OR 2.4, 95% CI1.07-5.38), highlighting the risks surrounding this period among deliveries at HAM maternity unit.…”
Section: Discussionsupporting
confidence: 92%
“…To the best of our knowledge, this is the first study to assess peri-neonatal mortality in STP, and it was undertaken within the context of a broader project on neonatal adverse birth outcomes (ABOs) in this LMIC [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, intestinal parasitic infections among pregnant women in Sao Tome and Principe have never been studied. Tis study was undertaken within the context of a broader project on the causes and risk factors contributing to neonatal mortality and adverse birth outcomes in STP [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…There is, however, a knowledge gap concerning the obstetric and perinatal characteristics of this major public health problem in this country. The authors have also studied these pregnant adolescents´ characteristics and factors associated with early childbearing in STP, whose results were published in another article [ 40 ].…”
Section: Introductionmentioning
confidence: 99%